Product Marketing Education and Branding Strengthening to Increase Sales Results Among Teenagers - Novfitri Landong Namora Sihombing; Zahra Hardiyanti; Lyscha Novitasari; Herlini Gani?; Jana Sandra (CV ODIS, 2022)
Marketing is basically a communication phenomenon because in marketing most of the activities are communication activities ranging from products designed and packaged to information about products that are disseminated to the wider community. , the problem does not stop there, marketing has followed a digitally controlled system known as e-commerce, and every business needs a strategy as a means of winning the competition and achieving goals. Strategy requires individuals who are smart in creating business concepts but also requires individuals who are brave and persistent and tenacious in implementing corporate ideals. Therefore, it is built starting from the individual level. It will not go well without qualified individuals, therefore human resources are the main key Community service activities are carried out to educate human resources who do not have very broad insight related to business practices and entrepreneurship, marketing, and marketing communications which are indispensable if you want to become business actors so that they will create resources that have creative, innovative, smart and ready businesses. compete competitively.